Puzzled by Your Care Receiver’s Refusal of Services? FCS2259/FY871, 11/2006 - Wilken, Carolyn S. (EDIS, 2006)
FCS-2259, a 2-page fact sheet by Carolyn Wilken, is the third in a series on caregiving and aging. Sometimes an elderly care receiver may refuse help or assistance from family, friends, or agencies. This publication lists some common reasons for this behavior, ranging from fears about accepting "welfare" to worries about losing independence. Published by the UF Department of Family, Youth and Community Sciences, November 2006.